Sonochemical synthesis of a copper reduced graphene oxide nanocomposite using honey and evaluation of its antibacterial and cytotoxic activities - Ismail, Nur Afini; Shameli, Kamyar; Mohamad Sukri, Siti Nur Amalina; Hara, Hirofumi; Teow, Sin-Yeang; Moeini, Hassan (Frontiers in Molecular Biosciences, 2022)
Presently, the arising of antimicrobial resistance disease and cancer cases are still intimidating humankind which could lead to mortality cases. The development of a combination between graphene-based materials and inorganic nanoparticles to enhance the properties of the nanomaterial was extensively explored nowadays. Hence, this study was focused on a facile preparation of copper/reduced graphene oxide (Cu/RGO) nanocomposite through the sonochemical method in the presence of honey. Australian honey was used as a capping agent and ascorbic acid acted as a reducing agent in nanocomposite production. The Cu/RGO nanocomposite was then characterized through UV-visible, XRD, HRTEM, and FTIR analysis. A uniform spherical shape of copper nanoparticles with a mean particle size of 2.20 ± 0.70 nm was found attached to the RGO surface in the nanocomposite. The cell viability of the antibacterial and cytotoxicity activity for the Cu/RGO nanocomposite have been investigated via minimum inhibition concentration (MIC) assay and MTS assay respectively. The nanocomposite shows better antibacterial activity toward the gram-positive bacteria compared to gram-negative and it also shows good killing activity toward the colorectal cancer cell.